Reciprocal Epistemic Failure in Ibn Ṭufayl's Ḥayy Ibn Yaqẓān: Extending Fricker's Hermeneutical Injustice to the Responsibility of the Knower - Zalikho Su'ada; Herdito Sandi Pratama; Meutia Irina Mukhlis (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
The epilogue of Ibn Ṭufayl's Ḥayy Ibn Yaqẓān has recently been read as a portrait of epistemic injustice, with Ḥayy cast as the victim of a society that rejects his testimony on account of his foreignness. This article argues that the reading is untenable and that its correction yields a more interesting result. The narrative does not show Ḥayy being rejected: he is brought to the island by a respected figure, received with honour, and heard attentively; what defeats him is not prejudice against his identity but the incapacity of his audience — and, decisively, it is Ḥayy himself who withdraws, apologises to the people of Salāmān, counsels them to hold fast to the literal Law, and returns to his island. The tale is therefore not a critique of epistemic exclusion but an endorsement of it, and it belongs to the tradition of epistemic elitism running from al-Fārābī through Ibn Bājja to Ibn Rushd. Applying Miranda Fricker's categories, the article shows that Ḥayy's case satisfies none of the conditions for systematic testimonial injustice, since he belongs to no stereotyped social type, and that the hermeneutical lacuna in the story lies with the community rather than with him. Rather than abandoning Fricker, the article proposes an extension: what the tale exhibits is reciprocal epistemic failure — a community deprived of the interpretive resources by which the philosopher's testimony could be received, and a philosopher who declines the responsibility of supplying them. Drawing on Medina and Pohlhaus, the article argues that Fricker's framework, which analyses the victim, requires supplementation by an account of the epistemic responsibility of the privileged knower. Ibn Ṭufayl, read against himself, supplies the case that demands it.